1, 25-dihydroxyvitamin D3 ameliorates high glucose-mediated proliferation, migration, and MCP-1 secretion of vascular smooth muscle cells by inhibiting MAPK phosphorylation. Issue 9 (September 2022) - Kaizu, Xu; Ying, Wu; Mei-fang, Wu; Li-ming, Lin
Objectives: To explore the impacts of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) on the proliferation, migration, and monocyte chemoattractant protein-1 (MCP-1) secretion of vascular smooth muscle cells (VSMCs) in a high glucose environment and its possible mechanism. Methods: We extracted VSMCs from the thoracic aorta of a male Sprague–Dawley rats before culturing them in a 25-mM glucose-containing medium in the presence or absence of 1, 25(OH)2 D3 (10 −9 –10 −7 M). Cell proliferation was determined by bromodeoxyuridine incorporation assays. Subsequently, cell migratory capacity was examined by performing a transwell assay. An enzyme-linked immunosorbent assay was conducted to assess MCP-1 levels. Protein levels of matrix metalloproteinase-9 (MMP-9), mitogen-activated protein kinases (MAPKs), cyclin D1, and phosphorylated MAPKs were determined by immunoblotting. Results: 1, 25(OH)2 D3 significantly suppressed the proliferation, migration, and MCP-1 secretion of VSMCs mediated by high glucose in a dose-dependent manner, diminished the enhanced protein expression of MMP-9 and cyclin D1, and attenuated MAPK phosphorylation. The p38 inhibitor SB203580 and ERK1/2 inhibitor PD98059 suppressed high glucose-mediated upregulation of MMP-9 and cyclin D1 protein expression and MCP-1 secretion, respectively. Conclusions: 1, 25(OH)2 D3 ameliorates high glucose-mediated proliferation, migration, and MCP-1 secretion of VSMCs by inhibiting MAPK phosphorylation, implying a potential therapeutic approach using 1, 25(OH)2 D3 for diabetic macrovascular complications.